2007
DOI: 10.1136/jcp.2005.031294
|View full text |Cite
|
Sign up to set email alerts
|

Mixed epithelial and stromal tumour of the kidney with luteinised ovarian stroma

Abstract: We report a case of a 9-cm mixed epithelial and stromal tumour of the kidney in an obese 70-year-old woman with diabetes. The ovarian-type stroma had a spindle cell component that was positive for progesterone receptors and had the hitherto unreported presence of abundant foci of luteinised stromal cells with characteristic immunohistochemical positivity to a-inhibin, calretinin, aromatase and gonadotropin-releasing hormone (GnRH) receptors. We conclude that the stromal component is identical to ovarian cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…This mixture of various types of these Müllerian epithelia can often be seen within a single tumor mass in MESTK [16]. In addition, the ovarian stroma of MESTK can infrequently reveal fibrous areas indistinguishable from corpora albicantia [15], and rarely, there may even be lutein stromal cells identical to those seen in the ovaries [4]. Such epithelial and stromal features are never seen in RATs.…”
Section: Discussionmentioning
confidence: 94%
“…This mixture of various types of these Müllerian epithelia can often be seen within a single tumor mass in MESTK [16]. In addition, the ovarian stroma of MESTK can infrequently reveal fibrous areas indistinguishable from corpora albicantia [15], and rarely, there may even be lutein stromal cells identical to those seen in the ovaries [4]. Such epithelial and stromal features are never seen in RATs.…”
Section: Discussionmentioning
confidence: 94%
“…52 The ovarian stromal components of both pancreatic mucinous cystic neoplasms and renal mixed epithelial stromal tumors are also reactive with inhibin. 4,48 Similarly, SF-1 reactivity in primary gonadal sex-cord stromal tumors may show staining in metastatic foci. 41,51,52 In summary of this tissue microarray study, we have shown that using an antibody panel comprised of chromogranin plus SF-1 and either calretinin or inhibin (while maintaining a Z2+ staining intensity threshold) is most effective in distinguishing adrenal cortical lesions from pheochromocytomas.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are case reports and series in the pathology literature [1][2][3]6,7,[9][10][11][12][13][14]16,17] there are few published reports describing the imaging findings of MEST [5,8,19]. To the best of our knowledge, the largest radiological study described the imaging features in three patients [5].…”
Section: Introductionmentioning
confidence: 94%
“…A strong association with oestrogen exposure was proposed. Of the 90 patients reported who had MEST [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18], almost all have been women [2,4]. Many of these patients were perimenopausal with a history of long-term oestrogen replacement at the time of diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%